Breeding biology and egg temperatures of Black-faced Brush-finches (Atlapetes melanolaemus), Neotropical montane songbirds (2016)
Black-faced Brush-finches (Atlapetes melanolaemus) are a common species restricted to the Andes of southern Peru and western Bolivia. We provide the first description of the breeding biology of this Neotropical montane passerine, including an analysis of incubation behavior and egg temperatures. We found 47 nests during seven breeding seasons (2007–2013) near Manu National Park, Peru. Nesting occurred in late July, peaked in early October, and continued into early December. All clutches consisted of two eggs, and the mean incubation period (14.8 ± 0.2 d) was relatively short compared with related species. Nest attentiveness increased and the length of foraging trips decreased as the incubation period progressed, but the number of foraging trips/day was constant. Egg temperatures when birds returned to incubate were negatively correlated with the duration of incubation bouts, whereas ambient temperature and the duration of the previous incubation bout were positively correlated with the duration of foraging bouts. Eggs were consistently incubated at lower temperatures (24-h mean = 32.1°C) than other Neotropical and temperate species. When incubating birds left nests, egg temperature dropped below the physiological zero temperature (24–27°C) in ~11 min. Nestlings had a high growth rate (k = 0.60) and a long nestling period (mean = 13.8 d) compared with related Neotropical and temperate emberizines. By showing that the duration of incubation and foraging bouts are affected by different intrinsic and extrinsic factors, we provide evidence that incubation is not only temporally dynamic, but also finely modifiable. Our results also suggest that embryos of high-elevation Neotropical songbirds are particularly resistant to ambient temperature extremes and low incubation temperatures, emphasizing the need for more studies of egg thermoregulation and its consequences for development, growth, and survival. We conclude that closely related species, both on different continents and at the same locations, may differ in parental care strategies and development regimes, cautioning against broad generalizations regarding species groups or geographic areas. © 2016 Association of Field Ornithologists